ANALYSIS OF SUSTAINABLE PERFORMANCE IN THE PALMYRA SUPPLY CHAIN USING CAUSAL-LOOP DIAGRAM - Ezar Amrullah; Elisa Kusrini; Sakbani Sakbani (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2023)
The study analyzed sustainable supply chain management performance in the Palmyra handicraft industry in Central Lombok. The study analyzed sustainability based on economic, social, and environmental performance attributes. Economic and environmental performance attributes used the SCOR 12 model, while social performance attributes were adopted from previous research. These performance attributes were modeled with causal-loop analysis to understand the interaction between performance attributes in influencing overall supply chain performance. This study explored critical factors in the Palmyra handicraft supply chain to gain sustainability. Support any stakeholders to make a strategic decision on the Palmyra supply chain. Theoretically, the contribution of this study is to expand the insight of sustainability in supply chain management in a small industry context.